Language Variations in the Comment Column of 'The Face Temulawak' Content on Tiktok Account @Emang His Name Dilan - Apriliya, Diyana; Asropah, Asropah; Andrian, Setia Naka (Journal of English Language and Education, 2026)
This study aims to describe the forms of language variations found in the comment column on The Face Temulawak content on the TikTok account Emang is called Dilan. The development of digital technology, especially TikTok, plays a key factor that encourages changes in the way of language in society. Language variations arise due to social factors and related to conditions that make language variations on social media more diverse today, especially in the TikTok application. In addition, the public is free to comment so that new languages can emerge that are not standard. This study uses a descriptive qualitative research method, with sociolinguistic studies. The data source consists of comments collected from the social media platform of the Emang account named Dilan. This research method applies the technique of watching and taking notes. The findings of this study reveal that there are variations, namely the variation of the slang there are 9 data, the variation of the abbreviation language there are 10 data, and the variation of the Indoglish language has 9 data.